OPTIMIZATION OF THE ABILITY TO REPORT ANNUAL SPT TAXPAYER OF PERSONAL PERSONS FOR EMPLOYEES OF IMMIGRATION OFFICE CLASS I TPI BENGKULU - Gunawan Ari Nursanto; Abharina Afiah Ghassani A (Polteknik Imigrasi, 2022)
There are still many Class I TPI Bengkulu Immigration Office employees who have not been able to operate e-filing, which results in employees being late in reporting their annual SPT by e-filing. The purpose of this Community Service activity (PKM) is to provide training and assistance to assist individual taxpayers, especially employees of the Class I Immigration Office TPI Bengkulu, in filling out and reporting the 1770s and 1770ss annual individual tax returns using e-filing. Community service is carried out using the Community Based Participatory Research (CBPR) method. The settlement techniques offered are through training approaches, discussions and/or questions and answers as well as practice. This training uses lecture and discussion techniques. The training that has been held has had an impact on increasing the knowledge and skills of the trainees in terms of tax reporting using e-filing from before who did not know the tax reporting mechanism. Through increasing the knowledge and skills of online tax reporting, TPI Class I Immigration Office employees report tax payable to the state. In the future, the implementation of community service can expand the target partners